Stability Analysis of Colluvial Slope under Different Rainfall Conditions. Issue 5 (August 2019) - Fan, RongQuan; Xiao, Hong; Liu, Teng; Ren, GuangMing; Wang, Bin; Chen, ZhongGuo
Abstract: Taking the accumulation slope of a reservoir abutment in western Sichuan as an example, this paper studies the influence of rainfall duration and rainfall intensity on slope stability with the help of GEO-SLOPE (SLOPE/W module) software according to saturated-unsaturated seepage theory and rainfall infiltration theory. The results show that when the rainfall intensity is constant, the slope stability decreases with the increase of rainfall duration, which presents a slightly slow-fast-slow pattern, and that the slope stability grandually dcreases with the increase of rainfall intensity under the same rainfall duration.